O protagonismo feminino vitoriano na ficção detetivesca - Moraes, Kátia Rosângela dos Santos (2023)
The political and economic development that took place in nineteenth-century English society led to a greater interest in literature, which, progressing on a large scale during this period, made possible the flourishing of the literary genre called the novel, in particular, the subgenre called detective fiction.Thus, this work aims to analyze the characterization of protagonists of the detective narratives The Female Detective (1864), by Andrew Forrester and Revelations of a Lady Detective (1864), by William Stephens Hayward, in order to identify the inconsistencies in their configuration. In the light of feminist critical studies, sometimes agreeing, sometimes partially or totally disagreeing, this work demonstrates the relevance of the discussion regard to the figure of the Victorian female detective, in order to understand the behavioral conflict generated by being in disagreement with the social rules relating to the women, in particular, the “cult of female domesticity”, that is the idea that the female sphere was limited to the domestic space. Since the aim of the authors approached by this study is to focus on the professional skills of their protagonists, we perceive a tendency to camouflage the subjectivity of the characters as a female being. However, we noticed that the protagonists build their identities by highlighting femininity markers, which are not those stipulated by Victorian social rules. Based on the assumptions that the characters represent real people in the fictional universe, we understand that the reader assimilates the discourses produced about women and the social expectations generated around them as true. Thus, the importance of feminist literary criticism is highlighted, which encourages the reader to review their usual expectations. Basic theorists will be revisited in order to substantiate the discussions, such as Tzvetan Todorov (2006), Jonathan Culler (1999), Terry Eagleton (2006), among others.